Let's talk Europe: Pastor Jan Paulsen, world president of the Seventh-day Adventist Church, met with youth ages 20-25 for an unscripted conversation (General Conference of Seventh-day Adventists, 2005)
El pastor Jan Paulsen, presidente mundial de la Iglesia Adventista del Séptimo Día, se reunió con jóvenes de entre 20 y 25 años para una conversación sin guion. Bono extra: Let's talk St Louis